2008
DOI: 10.1002/hup.961
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine‐induced reduction in activity mirrors decrements in cognitive and psychomotor performance

Abstract: What this paper addsWhat is already knownThe evaluation of psychotropic drug effects has been conducted utilising psychometric test batteries to assess changes in daytime cognition and psychomotor functioning and PSG to assess changes in sleep. Actigraphy is widely accepted as a non-invasive tool for assessing sleep-wake patterns in different groups. However, there is limited data to show that actigraphy can reliably measure the daytime and night-time characteristics of a CNS drug. What this study adds -This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…The hypotheses tested herein were that benzolamide, which remains an orphan drug since its first testing in humans more than 50 years ago and never tested under field conditions for AMS prevention, is effective in increasing arterial oxygenation and preventing AMS during a high‐altitude expedition. Underlying this proposed effectiveness and possible superiority of benzolamide over acetazolamide is the likelihood that benzolamide has fewer CNS side effects than acetazolamide, when tested in a rigorous double‐blinded placebo‐controlled fashion with an active comparator, lorazepam, known to alter CNS function (Dawson et al …”
Section: Introductionmentioning
confidence: 99%
“…The hypotheses tested herein were that benzolamide, which remains an orphan drug since its first testing in humans more than 50 years ago and never tested under field conditions for AMS prevention, is effective in increasing arterial oxygenation and preventing AMS during a high‐altitude expedition. Underlying this proposed effectiveness and possible superiority of benzolamide over acetazolamide is the likelihood that benzolamide has fewer CNS side effects than acetazolamide, when tested in a rigorous double‐blinded placebo‐controlled fashion with an active comparator, lorazepam, known to alter CNS function (Dawson et al …”
Section: Introductionmentioning
confidence: 99%
“…Lorazepam is a benzodiazepine with high affinity for gamma‐aminobutyric acid (GABA) receptors that negatively affects a broad range of cognitive functions (Stewart, 2005). The lorazepam challenge was chosen because its C max is well known and its deleterious effects on cognition in healthy adults are well described (Dawson et al ., 2008; Maruff et al ., 2006; Mintzer and Griffiths, 2003; Snyder et al . 2005; Stewart, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The present study had two main aims: (1) compare effect sizes of lorazepam vs. placebo groups at C max using means and standard errors generated by paired‐sample t ‐tests, RM‐ANOVA, and LMM; and (2) compare effect sizes of ascending slopes (baseline, 1 h, C max ) generated using t ‐tests of change from baseline scores, AUC, and LMM. Given that acute administration of benzodiazepines, such as lorazepam, is known to slow processing speed and reduce attention, memory, and executive function (Dawson et al ., 2008; Maruff et al ., 2006; Snyder et al ., 2005; Stewart, 2005), we hypothesized that performance on all of the cognitive tasks would decline to a greater extent under lorazepam than under placebo. We further hypothesized that, because LMM permits estimation of fixed effects independent of random effects, they would yield larger effect sizes on all tests at C max and over the ascending slopes.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians prefer BZD with an intermediate halflife to extensively sedating long half-life BZDs [42,43]. Lorazepam has been reported to impair motoric function in humans [8] and mice [11]. In the current study, mice were injected with lorazepam (0.5 mg/kg) in the afternoon, and next morning they were tested for motoric function using Rotarod apparatus.…”
Section: Bzd Injection and Motoric Testmentioning
confidence: 94%
“…One common problem with BZD therapy is that patients often experience motor incoordination and movement disorders. For example, BZDs increase the risk for falls [3][4][5], automobile accidents [6], slow motor reaction, and the inaccuracy of motor tasks [7][8][9]. Animal studies have also shown that diazepam and lorazepam provoke motoric deficit [10,11].…”
Section: Introductionmentioning
confidence: 99%